Investigating the Relationship of Sustainability Practices Dimensions Towards Green Campus Initiative in National Defence University of Malaysia - Mazura Hj. Mohaiyadin, Norlaila; Mardzuki, Khairunnisa; Ong Hai Liaw, Jessica; Wai Loong, Wong; Azan Ridzuan, Ahmad; Noor Azmi Hj. Zainol, Hj. (International Journal of Engineering and Technology, 2018)
The aim of this study is to investigate the relationship between sustainability practices from corporate governance, students, staff, society, companies and continuous improvement dimensions, and environment dimension. A sample of 188 respondents from administration, selected faculties and centres of the National Defence University of Malaysia participated in responding to the survey of this study. Researchers used the Pearson correlation analysis from the Statistical Package for the Social Sciences software. Results found that there are significant relationships between corporate governance, students, staff, society, companies and continuous improvement, and environment. This study is the new finding to the current research gap, where hypothesis testing is used and may also contribute to the Higher Education Institutions, either local or international to make the instrument of this study as a part of the key performance index for the green campus initiative.Â Â